Análisis del contenido de la revista televisiva matinal de canal 6 y su aceptación en los televidentes de la ciudad de Babahoyo - Vera Guerrero, Haydee Yamileth (2020)
The media have a number of contents within which is the family morning magazine, in channel 6 there is a morning program dedicated to disseminate reports and entertainment, after analyzing the objective it was found that these contents that are generated within of that means they are directed to housewives and for that reason the channels transmit new and popular subjects. At present, due to television competition, some morning programs have diminished the quality of their contents, which in some cases have the purpose of only generating a rating. This research aims to carry out a comparative analysis of the programs in question, to determine the influence that they can exert on the female population. The data collection techniques that have been used within this investigation have been the qualitative method and the observation sheet, the latter providing detailed information.